How useful are transect surveys for studying carnivores in the tropical rainforests of Borneo? - John, Mathai; Devcharan, Jathanna; J.W., Duckworth (National University of Singapore, 2013)
Transect surveys are a widely used tool in the study of wildlife populations. Here, we review different forms and objectives of transect surveys, discuss the need for and briefl y describe principles of good study design, and discuss various biological measurements employed in the study of carnivores in the rainforests of Borneo. We discuss the conservation value of these measurements, underlying assumptions in using different approaches, and why these assumptions cannot often be met in the study of Bornean carnivores. We argue that transect surveys are of little use as a stand-alone technique for carnivore studies in Borneo; numbers of encounters from genuinely random transects are too low to be amenable to quantitative analysis, whereas observations from non-random transects are biased and cannot be used for drawing any sort of wider inference. We consider approaches in which transect surveys could be implemented in conjunction with other techniques. In general, limited conservation resources could be better spent on other techniques and other measures that can usefully inform conservation.